Safety and Efficacy for the Combination of Alpha Lipoic Acid, Gingko Biloba, Vitamin C, Zinc, Magnesium, Vitamin B6, Methylcobalamin, Vitamin E and Chromium Picolinate for the Medical Management of Age Related Hearing Loss: Post Marketing Surveillance Study - Kiran, Dr. Mayuresh; Pawaskar, Mr. Lalit; Sheikh, Ms. Shaheen; Waghambare, Ms. Pramita (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Age related hearing loss is defined as a bilateral, progressive, symmetrical age-related sensorineural hearing loss, which is most pronounced at the higher frequencies. It is considered that oxidative stress has a central role in the pathology of age-related hearing loss so, this study was conducted to test the efficacy and safety for the combination of antioxidants for the treatment of age-related hearing loss. Methodology: This was a multi-centric study conducted at 11 clinical trial sites. Out of total 176 enrolled, 160 trial subjects completed the study. For efficacy assessment, 2 parameters were used including hearing related quality of life score and score obtained from hearing impairment questionnaire on day 0 (visit 1), 45 (visit 2) and 90 (visit 3). Results: At visit 1, the mean hearing related quality of life score was 4.437 increased to 5.725 at visit 2 and further increased to 6.906 at visit 3. At visit 2 and 3, the increase in hearing related quality of life score was 29.028% and 55.645% respectively as compared to baseline. The score obtained from hearing impairment questionnaire was 25.581 at visit 1 reduced to 16.200 and further reduced to 9.943 at visit 3. Conclusion: The combination of Alpha lipoic acid, Gingko biloba, Vitamin C, Zinc, Magnesium, Vitamin B6, Methyl cobalamin, Vitamin E and Chromium Picolinate can be used for the medical management of age related hearing loss.